HUBUNGAN BEBERAPA KELUHAN PUS DENGAN LAMA PEMAKAIAN IUD PADA AKSEPTOR AKTIF IUD DI KECAMATAN MIJEN KOTA SEMARANG TAHUN 2013 - Aditya Imam Efendi; Dharminto Dharminto; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2015)
IUDis along-term contraception andnon-hormonalcontraceptives. In 2012,the percentage ofusing IUD isstillthirdranks inIndonesia. The number ofIUD activeacceptorshas increased in DistrictMijenSemarang City, butstilla lot ofcouplesare reluctant to usethe IUDbecause ofside effects.The purposeofthis study was toanalyze the relationship betweenseveralcomplaintswithduration of useof activeIUDacceptorsin DistrictMijenSemarang City. This research isexplanatory researchwithcross sectional approach. The populationin this study were115activeIUDacceptorsandrecordedinBapermasandKBDistrict Mijen ofSemarang Cityin 2013study  that was conductedin14villages. Sampling was done bysimple random samplingas many as 53respondents. Data were analyzed descriptivelyandanalyticallyusingfisher exact testwith α = 5%. The results ofa descriptivestudyshowsthe biggest percentage ofcomplaintshemorrhage17.0%), abdominalpain(32.1%), disturbancecomplaintsintercourse(15.1%), complaintsof vaginal discharge(37.7%). Percentage of complaintsof bleedingoccurs inan IUDacceptorswithduration of use≤5year(100%), abdominalpainwas greater thanthe use≤5yearsold(70.6%) inIUDacceptors, complaints of interferencewithcoitusonduration of useof IUDacceptors≤5year(100%), complaintsof vaginal dischargeis greater thanthe use≤5yearsold(80.0%) inIUDacceptors. There is no significant correlation between the complaints of bleeding (p=0.100), abdominal pain (p=0.490), disturbance complaint intercourse (p=0.175) and complaints of vaginal discharge (p=1.000) with duration of use IUD (p>0.05)Recommended to women empowermentandfamily planning to perform interactive counseling about IUD contraception through the activities of the PKK, gathering or recitation.As well as interactive simulations as a venue for control and evaluation. For IUD acceptors required used against concern.